The Importance of Foraminifera of the Family Cassidulinidae for the Late Quaternary Paleoenvironmental Reconstructions Based on Sediment Cores from the Laptev Sea - Ovsepyan, Ya. S.; Averkina, N. O.; Taldenkova, E. E. (Paleontological Journal, 2019)
Three most common Arctic foraminiferal species of the family Cassidulinidae from the Laptev Sea sediment cores were analyzed for paleoenvironmental reconstructions. This paleontological study is focused on morphological characteristics of apertural elements and the wall structure. The species Cassidulina neoteretis is considered an indicator of the Atlantic influence in contrast to the Arctic species Cassidulina reniforme and Islandiella norcrossi.